Keefektifan Pemantapan Kemampuan Guru SMK dalam Menulis Proposal Penelitian Eksperimen - Prakoso, Albrian Fiky; Trisnawati, Novi; Soesatyo, Yoyok; Tjipto Subroto, Waspodo; Canda Sakti, Norida (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
Teacher's misunderstanding in compiling an experimental research proposal is one of the factors that causes teachers to be reluctant to conduct research. On the other hand, mentoring is also needed so that teachers have the convenience and are interested in conducting experimental research. The purpose of this Training in Community Service (In Indonesia called PKM) is to (1) provide teacher's understanding of experimental research, (2) provide assistance in developing the experimental research proposal framework, (3) provide, assistance in preparing experimental research proposals. Subjects in this PKM are teachers of IKIP Gedangan Vocational School and Surabaya IKIP Vocational School. The object of this PKM is the training of experimental research proposal writing. PKM implementation methods are broadly divided into 2 activities, namely the provision of material about experimental research with varied lecture methods and the practice of experimental research proposal writing simulation and presentation methods. The results obtained were quite effective because there was an increase in participants' understanding of the original 44% to 7%. There were also participants who still did not fully understand how the stages of experimental research started from problems, selection of control class and experimental class to data analysis. In the future, mentoring will be continued until the making of the experimental research report, considering the participants were very enthusiastic and curious by analyzing the data in experimental research.